Residential Customers Satisfaction with Public Water Provision in Ojota, Nigeria - Ohwo, Odafivwotu; Agusomu, Tano Dumoyei (European Scientific Journal, ESJ, 2018)
Customer satisfaction is a good measure of the quality of service rendered by an enterprise. Hence, this study analyzed the perception of residential customers’ satisfaction with public water provision in Ojota. The analyses was based on customers’ perception of ten selected satisfaction drivers, which were obtained by the administration of a set of structured questionnaire, administered to 400 households, using the systematic sampling technique. The data was analyzed using percentages and a customer satisfaction index (CSI) model. The calculated CSI was 2.54 points on a 5 point scale, which means that public water provision in Ojota is perceive as fairly satisfactory by the residential customers. In addition, only 12.21% of the customers are willing to pay for water, based on their overall perception of the services of the Lagos Water Corporation (LWC). This shows that the service of the LWC to its customers is inadequate. It is therefore recommended that the LWC should undertake a general overhaul of its operations and improve on customer services, which may improve customers’ willingness to pay for water provision and help the utility to improve on cost recovery and sustain adequate services to its customers.